Analisis Pengaruh CAR, FDR, NPF, dan Pertumbuhan DPK Terhadap Profitabilitas Pada Industri Bank Pembiayaan Rakyat Syariah di Indonesia Tahun 2011-2015 - Retno Wulandari; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This research aims to analyze the influence of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), and Third Party Fund Growth (DPK growth) to Return On Assets (ROA) of Islamic Rural Bank in Indonesia. All data that uses in this research contained from Sharia Banking Statistic (SPS) Bank Indonesia. This research used the quantitative approach method. The data analysis method used in this research is multiple linear regression analysis. Based on the results of this research showed that simultaneously CAR, FDR, NPF, and DPK growth had significant effect to ROA with significant value 0,000. Partially, CAR had not significant effect to ROA, but FDR, NPF, and DPK growth partially had significant effect to ROA. The ability of CAR, FDR, NPF, and DPK growth in explaining ROA ratio of 58%, and the remaining 42% was explained by other variables outside the model used in this research.